Functionalized TpPa-1 covalent organic framework as well as preparation method and application thereof
By ultrasonic modification of the TpPa-1 covalent organic frame material in alkaline solution, forming a porous structure and enhancing its adsorption ability, the problems of poor material stability and low adsorption efficiency in the prior art are solved, and the effect of efficient adsorption of a variety of heavy metal ions is achieved.
Patent Information
- Application Number
- CN202411944917.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
In the prior art, covalent organic frame materials have poor stability, limited adsorption sites and low adsorption efficiency for a variety of heavy metal ions in water purification, which limits their application expansion in actual water purification.
The TpPa-1 covalent organic frame substrate is ultrasonic modified by alkaline solutions (such as NaOH or KOH aqueous solution) to form a rich porous structure, increase the specific surface area, and enhance its adsorption capacity through the ion exchange of Na+ and K+.
The adsorption speed and adsorption capacity of TpPa-1 material have been significantly improved, and the adsorption effect is shown on single heavy metal ions or mixed heavy metal ions, which is suitable for commercial promotion.
Smart Images

Figure BDA0005213409540000061 
Figure HDA0005213409550000011 
Figure HDA0005213409550000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of environmentally friendly new materials, and specifically relates to a functionalized TpPa-1 covalent organic framework and a preparation method and application thereof. Background Art
[0002] Heavy metals (including lead, cadmium, chromium, copper, nickel, cobalt, manganese, etc.) are widely present in the environment. Heavy metals such as lead, cadmium, and chromium are not essential elements for human life and are highly toxic; heavy metals such as copper and nickel are essential trace elements for life. However, when the concentration of all heavy metal elements exceeds a certain range, they will cause harm to the human body and even be fatal. For example, although copper is an essential element for life, it is also toxic to organisms. Some areas near harbors have experienced incidents where oyster meat turned green due to copper pollution. Heavy metal ions are not easily degraded in the environment and are bioaccumulative. Although the concentration of heavy metal ions discharged from the outlet after sewage treatment is very small, they will continue to remain, accumulate, and migrate through the food chain after entering the ecosystem, posing a serious threat to human health and the ecosystem. When heavy metals exceed a certain concentration in the human body, they will inhibit the activity of biological enzymes, deform hemoglobin, and destroy biochemical reactions, thereby causing pathological changes in the body. At present, heavy metal ion pollution in water sources is a major problem facing drinking water safety. It is of great significance to study efficient, green and pollution-free treatment processes for removing various trace heavy metal ions in drinking water.
[0003] Adsorption has the advantages of low cost, green energy saving, environmental friendliness, and no toxic byproducts. It has been widely used in the treatment of heavy metal ion pollutants in water bodies. Traditional adsorbents have the disadvantages of low adsorption efficiency, small specific surface area, low adsorption capacity, and weak affinity for heavy metal ions. Metal organic framework materials (MOFs) have the characteristics of large specific surface area, high porosity and easy structure control, and are considered to be excellent metal ion adsorbents. However, MOFs materials face problems such as poor stability and limited adsorption sites in actual water purification applications. In contrast, covalent organic framework materials (COFs) are organic porous materials with a periodic network structure formed by light elements connected by covalent bonds. They not only have the advantages of high specific surface area, regular and orderly pores, and easy functional modification, but also have good thermal stability and chemical stability. They are a promising excellent adsorbent in the field of water purification. Imine COFs materials have high stability in acidic, alkaline and high temperature environments, and the materials themselves have good crystalline porous structures and relatively simple building blocks, becoming the main research object in the field of COFs materials. The porous structure and molecular framework of COFs materials determine its properties. Its topological structure can be controlled by rationally selecting functional organic monomers or introducing functional groups after synthesis to meet specific functions for specific applications. Therefore, researchers usually use the chelation between specific active groups and heavy metal ions to pre-design specific functional monomers to prepare functionalized COFs with specific structural pore sizes or introduce specific functional groups into the synthesized COFs structure to selectively remove heavy metal ions from contaminated water. However, although the functionalized COFs materials prepared by these methods can achieve highly selective adsorption of specific heavy metal ions, the adsorption efficiency of other heavy metal ions is low and the removal effect is poor, which greatly limits the application expansion of such materials in actual water purification. Summary of the invention
[0004] In view of the problems and shortcomings in the prior art, the object of the present invention is to provide a functionalized TpPa-1 covalent organic framework and its preparation and application.
[0005] Based on the above purpose, the present invention adopts the following technical solution:
[0006] The first aspect of the present invention provides a method for preparing a functionalized TpPa-1 covalent organic framework, comprising the following steps:
[0007] (1) Under the catalysis of scandium trifluoromethanesulfonate, p-phenylenediamine and trialdehyde phloroglucinol were allowed to react at room temperature to prepare the TpPa-1 covalent organic framework substrate;
[0008] (2) using an alkaline solution to ultrasonically modify the TpPa-1 covalent organic framework substrate prepared in step (1), and washing the modified substrate with water and methanol in sequence, and drying to obtain a functionalized TpPa-1 covalent organic framework material;
[0009] The alkaline solution is a NaOH aqueous solution or a KOH aqueous solution.
[0010] Preferably, the concentration of the alkaline solution is 0.1-2 mol / L.
[0011] Preferably, the drying temperature in step (2) is 50 to 100° C., and the drying time is 10 to 24 hours.
[0012] Preferably, in step (1), the molar ratio of p-phenylenediamine to trialdehyde phloroglucinol is 3:2, and the molar ratio of p-phenylenediamine to scandium trifluoromethanesulfonate is (25-100):1.
[0013] Preferably, in step (1), p-phenylenediamine and trialdehyde phloroglucinol are dissolved in a mixed solvent, and the mixed solvent is composed of 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of (1-5):1.
[0014] Preferably, after the reaction in step (1) is completed, the insoluble matter is separated from the reaction solution, and the insoluble matter is washed and dried to obtain the TpPa-1 covalent organic framework substrate.
[0015] More preferably, the detergent for washing the insoluble matter is at least one of methanol, ethanol and acetone.
[0016] The second aspect of the present invention provides a functionalized TpPa-1 covalent organic framework material prepared by the method of the first aspect.
[0017] The third aspect of the present invention provides the use of the functionalized TpPa-1 covalent organic framework material as described in the second aspect in the adsorption and removal of heavy metal ions in water.
[0018] Preferably, the heavy metal ions are one or more of cadmium ions, lead ions, chromium ions (trivalent), cobalt ions, copper ions, nickel ions and manganese ions.
[0019] More preferably, when the functionalized TpPa-1 covalent organic framework is used as a water adsorbent, 0.05 g to 10 g of the functionalized TpPa-1 material can be added per liter of water with a heavy metal ion concentration of 0.01 mg / L to 20 mg / L.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention uses an alkaline solution to perform ultrasonic modification on the TpPa-1 covalent organic framework substrate, so that a rich porous structure is formed on the surface of the TpPa-1 substrate, which effectively increases the specific surface area of the TpPa-1 substrate. + and K + Due to the ion exchange effect, the modified functionalized TpPa-1 materials (NaOH-TpPa-1 and KOH-TpPa-1) showed the advantages of fast adsorption rate and high adsorption capacity for single heavy metal ions or mixed heavy metal ions.
[0022] (2) Compared with the existing modified covalent organic framework materials for heavy metal ion adsorption, the method of preparing functionalized TpPa-1 materials at room temperature in the present invention is simpler to operate and has milder conditions, avoiding the damage of high temperature and high pressure to the substrate and the structure of the modified material. The entire synthesis process is time-saving and highly reproducible, easy to industrialize and suitable for commercial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 1 and 2. These are the X-ray diffraction (XRD) patterns of the functionalized TpPa-1 materials in Examples 1 and 2 of the present invention and the unmodified TpPa-1 substrate in Comparative Example 1.
[0024] Figure 2 These are scanning electron microscope (SEM) images of the functionalized TpPa-1 materials in Examples 1 to 2 of the present invention and the unmodified TpPa-1 substrate in Comparative Example 1; wherein a is a scanning electron microscope (SEM) image of the unmodified TpPa-1 substrate in Comparative Example 1; b is a scanning electron microscope (SEM) image of the NaOH-TpPa-1 functionalized material in Example 1; and c is a scanning electron microscope (SEM) image of the KOH-TpPa-1 functionalized material in Example 2.
[0025] Figure 3 It is a N2 adsorption-desorption curve (BET) diagram of the functionalized TpPa-1 material in Examples 1 to 2 of the present invention and the unmodified TpPa-1 substrate in Comparative Example 1.
[0026] Figure 4 These are the adsorption diagrams of mixed heavy metal ions by the functionalized TpPa-1 materials in Examples 1 to 2 of the present invention in a mixed multi-component system at different solution pH values; wherein a is the adsorption diagram of mixed heavy metal ions by the NaOH-TpPa-1 functionalized material in Example 1 at different solution pH values; and b is the adsorption diagram of mixed heavy metal ions by the KOH-TpPa-1 functionalized material in Example 2 at different pH values.
[0027] Figure 5These are the thermodynamic adsorption diagrams of seven heavy metal ions respectively by the functionalized TpPa-1 materials in Examples 1 to 2 of the present invention in a single heavy metal ion system; wherein a is the thermodynamic adsorption diagram of seven heavy metal ions respectively by the NaOH-TpPa-1 functionalized material in Example 1; and b is the thermodynamic adsorption diagram of seven heavy metal ions respectively by the KOH-TpPa-1 functionalized material in Example 2.
[0028] Figure 6 These are the kinetic adsorption diagrams of seven heavy metal ions respectively by the functionalized TpPa-1 materials in Examples 1 to 2 of the present invention in a single heavy metal ion system; wherein a is the kinetic adsorption diagram of seven heavy metal ions respectively by the NaOH-TpPa-1 functionalized material in Example 1; and b is the kinetic adsorption diagram of seven heavy metal ions respectively by the KOH-TpPa-1 functionalized material in Example 2.
[0029] Figure 7 These are the adsorption diagrams of mixed heavy metal ions at different initial concentrations by the functionalized TpPa-1 materials in Examples 1 to 2 of the present invention in a mixed multi-component system; wherein a is the adsorption diagram of the NaOH-TpPa-1 functionalized material in Example 1 for 0.01, 0.05 and 0.1 mg / L of mixed heavy metal ions, respectively; and b is the adsorption diagram of the KOH-TpPa-1 functionalized material in Example 2 for 0.01, 0.05 and 0.1 mg / L of mixed heavy metal ions, respectively. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through embodiments in combination with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0032] (I) Preparation of functionalized TpPa-1 covalent organic framework materials
[0033] Example 1
[0034] A method for preparing a functionalized TpPa-1 covalent organic framework material comprises the following steps:
[0035] (1) Weigh 126.2 mg of trialdehyde phloroglucinol and 97.3 mg of p-phenylenediamine into a 50 mL conical flask, add 19.2 mL of 1,4-dioxane and 4.8 mL of 1,3,5-trimethylbenzene, dissolve them by ultrasonication, and allow to react at room temperature for 15 min to obtain solution A;
[0036] (2) adding 18 mg of scandium trifluoromethanesulfonate to solution A, dissolving it by ultrasonication, and allowing it to react at room temperature for 15 min to obtain solution B;
[0037] (3) The insoluble matter was separated by centrifugation from solution B, washed three times by centrifugation with methanol, and dried under vacuum at 80° C. for 12 h. The obtained material was called TpPa-1 substrate;
[0038] (4) Weigh 300 mg of TpPa-1 substrate and disperse it in 300 mL of 1 mol / L NaOH aqueous solution. Ultrasonicate for 30 min, centrifuge and wash with water and methanol three times respectively, and vacuum dry at 80 °C for 12 h. The obtained material is recorded as NaOH-TpPa-1 functionalized material.
[0039] Example 2
[0040] A method for preparing a functionalized TpPa-1 covalent organic framework is basically the same as that of Example 1, except that the alkaline solution modifier in step (4) is replaced by KOH from NaOH, and the obtained material is recorded as KOH-TpPa-1 functionalized material.
[0041] Comparative Example 1
[0042] A method for preparing an unmodified TpPa-1 covalent organic framework substrate, the preparation method is substantially the same as that of Example 1, except that step (4) is omitted.
[0043] Comparative Example 2
[0044] A method for preparing a functionalized TpPa-1 covalent organic framework is basically the same as that of Example 1, except that the NaOH aqueous solution in step (4) is replaced with ammonia water, and the obtained material is recorded as a functionalized NH4OH-TpPa-1 material.
[0045] Comparative Example 3
[0046] A method for preparing a functionalized TpPa-1 covalent organic framework is basically the same as that of Example 1, except that the NaOH aqueous solution in step (4) is replaced with a neutral NaCl solution, and the obtained material is recorded as a functionalized NaCl-TpPa-1 material.
[0047] Comparative Example 4
[0048] A method for preparing a functionalized TpPa-1 covalent organic framework is basically the same as that of Example 1, except that the NaOH aqueous solution in step (4) is replaced with a neutral KCl solution, and the obtained material is recorded as a functionalized KCl-TpPa-1 material.
[0049] (II) Structural characterization of functionalized TpPa-1 materials
[0050] The crystal structure, surface morphology and specific surface area of the functionalized TpPa-1 covalent organic frameworks (NaOH-TpPa-1, KOH-TpPa-1) prepared in Examples 1 to 2 and the unmodified TpPa-1 substrate prepared in Comparative Example 1 were characterized by X-ray diffractometer (XRD), scanning electron microscopy (SEM) and N2 adsorption-desorption experiment (BET diagram).
[0051] Figure 1 Figure 3 is the XRD diagram of the functionalized TpPa-1 covalent organic framework (NaOH-TpPa-1 and KOH-TpPa-1) prepared in Examples 1 to 2 and the unmodified TpPa-1 substrate prepared in Comparative Example 1. It can be seen from the figure that diffraction peaks are observed at 4.8°, 8.4°, 12.7°, 14.6° and 27.0° for the three materials, NaOH-TpPa-1, KOH-TpPa-1 and unmodified TpPa-1 substrate, which are respectively caused by the reflection of the
[100] ,
[110] ,
[111] ,
[120] and
[001] crystal planes of the materials, and the intensity of the diffraction peaks does not change significantly, which indicates that the unmodified TpPa-1 substrate and the functionalized TpPa-1 material are successfully prepared, and the modification treatment of the TpPa-1 substrate with NaOH or KOH does not change the crystal structure of the original covalent organic framework.
[0052] Figure 2 1 is a scanning electron microscope (SEM) image of the functionalized TpPa-1 material prepared in Examples 1 and 2 and the unmodified TpPa-1 substrate prepared in Comparative Example 1. The unmodified TpPa-1 substrate in Comparative Example 1 ( Figure 2 a), NaOH-TpPa-1 material of Example 1 ( Figure 2 b) and the KOH-TpPa-1 material of Example 2 ( Figure 2 c) By Figure 2a It can be seen that the unmodified TpPa-1 substrate is an agglomerate of spherical particles, with no obvious porosity on the surface, a relatively dense structure, and a particle size of about 1 μm; the surface morphology of the NaOH-TpPa-1 functionalized material obtained after NaOH modification is very different from that of the unmodified TpPa-1 material. The NaOH-TpPa-1 material is a spherical particle with a relatively rough surface and a rich porous structure, and the particle size is about 1 μm; the morphology of the KOH-TpPa-1 functionalized material obtained after KOH modification is similar to that of the NaOH-TpPa-1 functionalized material, and it also presents spherical particles with a rough surface and a rich porous structure, and the particle size is about 1 μm.
[0053] Figure 3 The specific surface areas of the functionalized TpPa-1 covalent organic frameworks (NaOH-TpPa-1 and KOH-TpPa-1) prepared in Examples 1 to 2 and the unmodified TpPa-1 substrate prepared in Comparative Example 1 are shown in Table 1. The BET specific surface areas of the unmodified TpPa-1 substrate, the functionalized NaOH-TpPa-1, and the functionalized KOH-TpPa-1 materials are calculated to be 47.1 m 2 / g, 138.2m 2 / g and 107.5m 2 / g. This result shows that both NaOH and KOH modification treatments effectively increased the specific surface area of the TpPa-1 substrate. Figure 2 The morphology analysis showed that this may be due to the modification treatment of NaOH and KOH which resulted in more microporous structures in the TpPa-1 substrate, which was beneficial to improving the adsorption capacity of heavy metal ions.
[0054] (III) Study on the adsorption performance of various heavy metal ions in water by functionalized TpPa-1 materials prepared under different modification conditions
[0055] The adsorption performance of 7 mixed heavy metal ions in water was evaluated for the TpPa-1 covalent organic framework materials prepared in Examples 1 to 2 and Comparative Examples 1 to 4. The specific experimental process was as follows: a certain mass of metal salts (cadmium chloride (CdCl2), lead nitrate (Pb(NO3)2, chromium trichloride (CrCl3), cobalt chloride hexahydrate (CoCl2·6H2O), copper chloride (CuCl2), nickel chloride (NiCl2) and manganese chloride (MnCl2)) were weighed and dissolved in water at pH = 2, and heavy metal ion aqueous solutions with concentrations of 1000 mg / L were prepared as stock solutions, and the stock solutions of heavy metal ions were diluted with pure water to prepare a mixed solution of 7 heavy metal ions with a concentration of 0.1 mg / L and a pH of 6 as a working solution; 3 mg of the TpPa-1 covalent organic framework materials prepared in Examples 1 to 2 and Comparative Examples 1 to 4 were weighed in 50 mL centrifuge tubes, and 30 mL of A 0.1 mg / L aqueous solution of seven mixed heavy metal ions was oscillated at room temperature for 12 hours, and then the centrifuge tube was centrifuged at 10,000 rpm for 5 minutes. The supernatant was taken and the content of heavy metal ions in the supernatant was determined by ICP-MS, and the equilibrium adsorption rate of TpPa-1 covalent organic framework material for heavy metal ions was calculated.
[0056] The calculation formula of equilibrium adsorption rate is as follows:
[0057] Adsorption rate % = (c0-c t ) / c0×100%
[0058] Among them, c0 (mg / L) and c t (mg / L) refer to the initial concentration of heavy metal ions and the concentration of heavy metal ions in the system solution at time t, respectively.
[0059] The specific adsorption results are shown in Table 1:
[0060] Table 1 Adsorption rates of the materials prepared in Examples 1 to 2 and Comparative Examples 1 to 4 for 7 heavy metal ions in the mixed solution
[0061]
[0062] As can be seen from Table 1, the unmodified TpPa-1 substrate prepared in Comparative Example 1 has a poor adsorption effect on 7 heavy metal ions in water, with an adsorption rate of 10.7% to 35.2%. Compared with the unmodified TpPa-1 substrate prepared in Comparative Example 1, the functionalized TpPa-1 covalent organic frameworks (NaOH-TpPa-1 and KOH-TpPa-1) prepared in Examples 1 to 2 all show excellent adsorption effects on 7 heavy metal ions in water, with adsorption rates of 98.4% to 100% and 97.2% to 100%, respectively. In addition, in Comparative Examples 2 to 4, other solutions (such as ammonia, NaCl and KCl) were used as modifiers to modify the TpPa-1 substrate, and it was found that the prepared functionalized TpPa-1 covalent organic frameworks had poor adsorption effects on 7 heavy metal ions in water. The above results show that the modification of TpPa-1 substrate by NaOH or KOH significantly improves the adsorption capacity of the original substrate for various heavy metal ions, and is far superior to the adsorption effect of functionalized TpPa-1 prepared by using other commonly used alkaline solutions such as ammonia or neutral solution as modifiers. This may be due to the effective increase in the specific surface area of TpPa-1 material by the modification of NaOH and KOH and the formation of Na in the porous TpPa-1 material. + and K + Due to the dual role of ion channels.
[0063] (IV) Study on the adsorption process of various heavy metal ions by functionalized TpPa-1 covalent organic framework materials
[0064] The functionalized TpPa-1 materials prepared in Example 1 (NaOH-TpPa-1) and Example 2 (KOH-TpPa-1) are used as experimental materials to study the adsorption process of various heavy metal ions by the materials of the present invention.
[0065] 1. Study on the influence of adsorption solution pH
[0066] (1) Experimental methods
[0067] A certain amount of metal salts (cadmium chloride (CdCl2), lead nitrate (Pb(NO3)2), chromium trichloride (CrCl3), cobalt chloride hexahydrate (CoCl2·6H2O), copper chloride (CuCl2), nickel chloride (NiCl2) and manganese chloride (MnCl2)) were weighed and dissolved in water at pH = 2. A 1000 mg / L heavy metal ion aqueous solution was prepared as a stock solution. The stock solution was then diluted with pure water to prepare a mixed solution of the seven heavy metal ions with a concentration of 0.1 mg / L as the working solution. The pH of the working solution was adjusted with 1 mol / L HCl or NaOH to obtain 0.1 mg / L mixed heavy metal ion working solutions with different pH values (4, 5, 6, 7, 8); 3 mg of functionalized TpPa-1 material was accurately weighed and placed in a 50 mL centrifuge tube, and then 30 mL of 0.1 mg / L aqueous solutions of 7 mixed heavy metal ions with different pH values were added thereto, respectively, and the mixture was oscillated and adsorbed at room temperature for 12 h; the centrifuge tube was centrifuged at 10,000 rpm for 5 min, and the supernatant was taken and the content of heavy metal ions was determined by ICP-MS.
[0068] (2) Results Analysis
[0069] Figure 4 They are respectively NaOH-TpPa-1 (prepared in Example 1 in the mixed multi-component system Figure 4 a) and KOH-TpPa-1 (prepared in Example 2) Figure 4 b) Adsorption diagram of seven mixed heavy metal ions by functionalized TpPa-1 material at different solution pH. Figure 4 It can be seen from a and 4b that when the solution pH = 4, the two functionalized TpPa-1 materials NaOH-TpPa-1 and KOH-TpPa-1 have obvious adsorption effects on 7 heavy metal ions, and the adsorption rates are 14.2% to 90.4% and 13.0% to 90.4%, respectively, which are better than the adsorption effect of the unmodified TpPa-1 substrate on 7 heavy metal mixed ions (the adsorption rate is 0.7% to 33.2% when pH = 4, and the adsorption rate is shown in Comparative Example 1 in Table 1 when pH = 6). When the solution pH is in the range of 5 to 8, the adsorption capacity of NaOH-TpPa-1 and KOH-TpPa-1 materials is significantly enhanced, and basically all can achieve complete adsorption of 7 heavy metal mixed ions. The above results show that the functionalized TpPa-1 materials such as NaOH-TpPa-1 and KOH-TpPa-1 prepared by the present invention can achieve efficient adsorption and removal of multiple mixed heavy metal ions in water within a wide pH range.
[0070] 2. Study on thermodynamic adsorption performance
[0071] (1) Experimental methods
[0072] Weigh a certain amount of metal salts (cadmium chloride (CdCl2), lead nitrate (Pb(NO3)2), chromium trichloride (CrCl3), cobalt chloride hexahydrate (CoCl2·6H2O), copper chloride (CuCl2), nickel chloride (NiCl2) and manganese chloride (MnCl2)) and dissolve them in water at pH = 2, prepare heavy metal ion aqueous solutions with a concentration of 1000 mg / L as stock solutions, and then dilute the stock solutions with pure water to prepare single heavy metal ion standard solutions (pH = 6) with concentrations of 0.01, 0.05, 0.1, 0.5, 1, 5, and 10 mg / L as working solutions; accurately weigh 3 mg The NaOH-TpPa-1 or KOH-TpPa-1 functionalized material was placed in a 50 mL centrifuge tube, and then 30 mL of a single heavy metal ion aqueous solution with different initial concentrations was added thereto, and the mixture was oscillated and adsorbed at room temperature for 12 hours; the centrifuge tube was centrifuged at 10,000 rpm for 5 minutes, and the supernatant was taken to determine the content of metal ions using ICP-MS, and the equilibrium adsorption amount of the seven heavy metal ions was calculated. The calculation formula for the equilibrium adsorption amount is as follows:
[0073] Q=(c0-c t )v / m
[0074] Where Q (mg / g) refers to the adsorption capacity of the adsorbent material, c0 (mg / mL) and c t (mg / mL) refer to the initial concentration of heavy metal ions and the concentration of ions in the system solution at time t, v (mL) refers to the volume of the adsorption solution, and m (g) refers to the mass of the adsorption material.
[0075] (2) Results Analysis
[0076] Figure 5 5a and 5b are the thermodynamic adsorption curves of the NaOH-TpPa-1 functionalized material prepared in Example 1 and the KOH-TpPa-1 functionalized material prepared in Example 2 for 7 single heavy metal ions in water. It can be seen from the figure that with the increase of initial concentration, the adsorption amount of 7 heavy metal ions on NaOH-TpPa-1 and KOH-TpPa-1 functionalized materials also increases. When the initial concentration of heavy metal ions is 10 mg / L, the NaOH-TpPa-1 material has an adsorption capacity of 100% except for Pb 2+ The adsorption of Pb by KOH-TpPa-1 has not yet reached saturation, while the adsorption of the other six heavy metal ions has basically reached saturation. 2+ and Cr 3+ The adsorption of Pb did not reach saturation, while the adsorption of the other five heavy metal ions basically reached saturation. The equilibrium adsorption amounts of these seven heavy metal ions on the NaOH-TpPa-1 functionalized material were as follows: 2+ >Cr 3+ >Cu2+ ≈Cd 2+ >Co 2+ ≈Ni 2+ ≈Mn 2+ , the equilibrium adsorption amount of Pb in KOH-TpPa-1 functionalized material is: 2+ >Cr 3+ >Cu 2+ ≈Cd 2+ ≈Co 2+ >Ni 2+ ≈Mn 2+ , it can be found that Pb 2+ and Cr 3+ The adsorption capacity on NaOH-TpPa-1 and KOH-TpPa-1 functionalized materials was strong, especially for Pb 2+ The adsorption capacity is the strongest.
[0077] 3. Kinetic adsorption performance study
[0078] (1) Experimental methods
[0079] Weigh a certain amount of metal salts (cadmium chloride (CdCl2), lead nitrate (Pb(NO3)2), chromium trichloride (CrCl3), cobalt chloride hexahydrate (CoCl2·6H2O), copper chloride (CuCl2), nickel chloride (NiCl2) and manganese chloride (MnCl2)) and dissolve them in water at pH = 2, prepare heavy metal ion aqueous solutions with a concentration of 1000 mg / L as stock solutions, and then dilute the stock solutions with pure water to prepare single heavy metal ion standard solutions with a concentration of 0.1 mg / L (pH = 6) as working solutions; accurately weigh 3 mg of NaOH-TpPa-1 or KOH-TpPa-1 functionalized material was placed in a 50 mL centrifuge tube, and then 30 mL of 0.1 mg / L of a single heavy metal ion was added thereto, and different reaction times (10 s, 20 s, 30 s, 1 min, 5 min, 10 min, 20 min, 30 min, 60 min) of oscillation adsorption were performed at room temperature; the centrifuge tube was centrifuged at 10000 rpm for 5 min, and the supernatant was taken to determine the content of metal ions by ICP-MS, and the equilibrium adsorption amount of the seven heavy metal ions was calculated respectively. The calculation formula of the equilibrium adsorption amount is as follows:
[0080] Q=(c0-c t )v / m
[0081] Where Q (mg / g) refers to the adsorption capacity of the adsorbent material, c0 (mg / mL) and c t (mg / mL) refer to the initial concentration of heavy metal ions and the concentration of ions in the system solution at time t, v (mL) refers to the volume of the adsorption solution, and m (g) refers to the mass of the adsorption material.
[0082] (2) Results Analysis
[0083] Figure 6 a and 6b are the kinetic adsorption curves of NaOH-TpPa-1 and KOH-TpPa-1 functionalized materials prepared in Example 1 and Example 2 for seven single heavy metal ions in water. Figure 6 As can be seen in a, the NaOH-TpPa-1 functionalized material exhibits a fairly fast adsorption rate for these seven heavy metal ions, except for Cr 3+ In addition, the adsorption rates of NaOH-TpPa-1 for the other six heavy metal ions were all above 95% in just 20 seconds. The adsorption of these six heavy metal ions reached equilibrium within 5 minutes. At 60 minutes, the adsorption of Cr 3+ The adsorption of these 7 heavy metal ions by KOH-TpPa-1 functional material is basically the same as that of NaOH-TpPa-1 functional material. Figure 6 b It can be seen that KOH-TpPa-1 exhibits a faster adsorption rate for the seven heavy metal ions than NaOH-TpPa-1, which takes only 10 s. 2+ , Pb 2+ 、Co 2+ , Cu 2+ 、Ni 2+ , Mn 2+ and Cr 3+ The adsorption rates of Cr 3+ In addition, the adsorption of the other six heavy metal ions by KOH-TpPa-1 material can reach equilibrium within 5 minutes, and the adsorption of Cr 3+ The adsorption can reach 91.6%. The above results show that NaOH-TpPa-1 and KOH-TpPa-1 functionalized materials have a faster adsorption rate and stronger adsorption capacity for 7 heavy metal ions in water.
[0084] 4. Adsorption and removal experiments of mixed heavy metal ions with different initial concentrations
[0085] (1) Experimental methods
[0086] A certain amount of metal salts (cadmium chloride (CdCl2), lead nitrate (Pb(NO3)2), chromium trichloride (CrCl3), cobalt chloride hexahydrate (CoCl2·6H2O), copper chloride (CuCl2), nickel chloride (NiCl2) and manganese chloride (MnCl2)) were weighed and dissolved in water at pH = 2, and heavy metal ion aqueous solutions with a concentration of 1000 mg / L were prepared as stock solutions. The stock solutions were then diluted with pure water to prepare seven heavy metal ion mixed standard solutions (pH = 6) with concentrations of 0.01, 0.05, and 0.1 mg / L, respectively, as working solutions; in the mixed multi-component system of seven heavy metal ions, 3 mg of NaOH-TpPa-1 or KOH-TpPa-1 functionalized materials were accurately weighed and placed in 50 mL centrifuge tubes, and then 30 mL of The mixed standard solutions of heavy metal ions with concentrations of 0.01, 0.05, and 0.1 mg / L were shaken and adsorbed at room temperature for 12 h. The centrifuge tube was centrifuged at 10,000 rpm for 5 min, and the supernatant was taken for determination of the content of heavy metal ions by ICP-MS. The adsorption and removal effects of NaOH-TpPa-1 or KOH-TpPa-1 functionalized materials on the seven heavy metal ions were calculated. The results are shown in the figure. Figure 7 shown.
[0087] (2) Results Analysis
[0088] Figure 7 The figure shows the adsorption effect of NaOH-TpPa-1 or KOH-TpPa-1 functionalized materials on seven heavy metal ions with different initial concentrations in the mixed multi-element system. It can be seen from the figure that in the initial concentration range of 0.01 to 0.1 mg / L, the adsorption of Cd by NaOH-TpPa-1 material is 2+ , Pb 2+ Cr 3+ 、Co 2+ , Cu 2+ 、Ni 2+ and Mn 2+ The adsorption rates of KOH-TpPa-1 material for Cd 2 + , Pb 2+ Cr 3+ 、Co 2+ , Cu 2+ 、Ni 2+ and Mn 2+The adsorption rates are 99.8-100%, 100%, 88.3-93.4%, 98.7-99.9%, 97.8-100%, 98.3-99.8% and 98.8-100%, respectively. After adsorption treatment by NaOH-TpPa-1 and KOH-TpPa-1 functionalized materials, the residual concentrations of the seven heavy metal ions in the solution are much lower than the limit values of these heavy metal ions in the national standard GB 5749-2022 "Sanitary Standards for Drinking Water". The results fully show that the functionalized TpPa-1 material synthesized by the present invention shows good removal effect on multiple single heavy metal ions and multiple heavy metal ions in mixed multi-coexistence systems, and has good practical application value.
[0089] In summary, the present invention effectively overcomes the deficiencies in the prior art and has a high industrial utilization value. The above embodiments serve to illustrate the substantive content of the present invention, but do not limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a functionalized TpPa-1 covalent organic framework, characterized in that: The steps include: (1) Under the catalysis of scandium trifluoromethanesulfonate, p-phenylenediamine and trialdehyde phloroglucinol were allowed to react at room temperature to prepare the TpPa-1 covalent organic framework substrate; (2) using an alkaline solution to ultrasonically modify the TpPa-1 covalent organic framework substrate prepared in step (1), washing it with water and methanol in sequence, and drying it to obtain a functionalized TpPa-1 covalent organic framework; The alkaline solution is a NaOH aqueous solution or a KOH aqueous solution.
2. The preparation method according to claim 1, characterized in that: The concentration of the alkaline solution is 0.1-2 mol / L.
3. The preparation method according to claim 2, characterized in that: The drying temperature of step (2) is 50-100° C., and the drying time is 10-24 hours.
4. The preparation method according to claim 1, characterized in that: In step (1), the molar ratio of p-phenylenediamine to trialdehyde phloroglucinol is 3:2, and the molar ratio of p-phenylenediamine to scandium trifluoromethanesulfonate is (25-100):
1.
5. The preparation method according to claim 4, characterized in that: In step (1), p-phenylenediamine and trialdehyde phloroglucinol are dissolved in a mixed solvent, wherein the mixed solvent is composed of 1,4-dioxane and 1,3,5-trimethylbenzene in a volume ratio of (1-5):
1.
6. The preparation method according to claim 5, characterized in that: After the reaction in step (1) is completed, the insoluble matter is separated from the reaction solution, and the insoluble matter is washed and dried to obtain the TpPa-1 covalent organic framework substrate.
7. The preparation method according to claim 6, characterized in that: The detergent for washing the insoluble matter is at least one of methanol, ethanol and acetone.
8. A functionalized TpPa-1 covalent organic framework material prepared by the method according to any one of claims 1 to 7.
9. Use of the functionalized TpPa-1 covalent organic framework material according to claim 8 in the adsorption and removal of heavy metal ions in water.
10. The use according to claim 9, characterized in that: The heavy metal ions are one or more of cadmium ions, lead ions, chromium ions, cobalt ions, copper ions, nickel ions and manganese ions.
Citation Information
Patent Citations
Biological composite material based on covalent organic framework material (COFs) as well as preparation and application of biological composite material
CN117430766A
Preparation method and application of polymer-based covalent organic framework film
CN119158427A